2022
DOI: 10.1186/s40538-022-00336-w
|View full text |Cite
|
Sign up to set email alerts
|

Whole genome-wide analysis of DEP family members in sheep (Ovis aries) reveals their potential roles in regulating lactation

Abstract: Background Sheep milk is an attractive nutritional and functional food source. Some Dishevelled, Egl-10 and pleckstrin (DEP) domain-containing proteins can regulate lactation performance in mammals. However, systematic study of the role of sheep DEP family members in regulating lactation is currently lacking. This study aimed to reveal the roles of sheep DEP family members in lactation by exploring their genetic characteristics and functional features at the whole genome-wide level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…DEPDC5 or DEP domain containing 5 is a gene located on OAR17 and involved in stimulus response and associated with growth traits [ 115 ]. Whole-genome analyses [ 116 ] have also shown that this gene family plays a role in the regulation of lactation in sheep. On OAR22, CFAP46 or cilia and flagella associated protein 46, has been associated to lactose content [ 117 ] whereas RBM34 or RNA-binding protein 34 gene on OAR25 has role in nucleic acid binding and nucleotide binding, and it was found by GWAS study on cattle to be associated with milk yield [ 118 ].…”
Section: Discussionmentioning
confidence: 99%
“…DEPDC5 or DEP domain containing 5 is a gene located on OAR17 and involved in stimulus response and associated with growth traits [ 115 ]. Whole-genome analyses [ 116 ] have also shown that this gene family plays a role in the regulation of lactation in sheep. On OAR22, CFAP46 or cilia and flagella associated protein 46, has been associated to lactose content [ 117 ] whereas RBM34 or RNA-binding protein 34 gene on OAR25 has role in nucleic acid binding and nucleotide binding, and it was found by GWAS study on cattle to be associated with milk yield [ 118 ].…”
Section: Discussionmentioning
confidence: 99%